GAYA BAHASA SINDIRAN DALAM KOLOM KOMENTAR AKUN INSTAGRAM AZIZAH SALSHA (PENDEKATAN STILISTIKA) - Wa Ode Halfian; Ratna Wati; Sahur Saerudin (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
This study aims to describe the type of satirical language style in the comment column of Azizah Salsha's Instagram account. This study uses the theory of Gorys Keraf, with a qualitative descriptive research method. The data of this research is in the form of comments from netizens in the comment column of Azizah Salsha's Instagram. The collection of research data was carried out using reading techniques and documentation. The results of the study showed that the types of satirical language styles of netizens in the comment column of Azizah Salsha's Instagram account on September 2 - September 9, 2024, found 3 (three) types of sarcastic language styles, namely irony, cynicism, and sarcasm. The results of the analysis contained 38 (thirty-eight) data, namely 1 (one) style of irony language, 17 (seventeen) styles of cynicism language, and 20 (twenty) styles of sarcasm language.